Access to treatment with controlled medicines rationale and recommendations for neutral, precise, and respectful language. (December 2017) - Scholten, W.; Simon, O.; Maremmani, I.; Wells, C.; Kelly, J.F.; Hämmig, R.; Radbruch, L.
Abstract: The European Pain Federation EFIC, the International Association for Hospice and Palliative Care, International Doctors for Healthier Drug Policies, the Swiss Romandy College for Addiction Medicine, the Swiss Society of Addiction Medicine, and the World Federation for the Treatment of Opioid Dependence called on medical journals to ensure that authors always use terminology that is neutral, precise, and respectful in relation to the use of psychoactive substances. It has been shown that language can propagate stigma, and that stigma can prevent people from seeking help and influence the effectiveness of social and public-health policies. The focus of using appropriate terminology should extend to all patients who need controlled medicines, avoiding negative wording. A narrow focus on a few terms and medical communication only should be avoided. The appropriateness of terms is not absolute and indeed varies between cultures and regions and over time. For this reason, it is important that communities establish their own consensus of what is 'neutral', 'precise', and 'respectful'. We identified twenty-three problematic terms (most of them we suggest avoiding) and their possible alternatives. The use of appropriate language improves scientific quality of articles and increases chances that patients will receive the best treatment and that government policies on psychoactive substance policies will be rational. Highlights: Wording about substance use disorder and psychoactive substances should be appropriate. Medical journals should request authors to eliminate terms that do not meet this standard. Inappropriate terms can induce biases negatively influencing social and public-health policies. Use of appropriate language increases chances that patients will receive the best treatment. Use of appropriate language increases chances for rational policies on psychoactive substances.